Development and Preliminary Clinical Validation of the Vitaltrack Early Warning Score Prototype for Integrated Inpatient Monitoring - Iffah Kurniyawati; Sri Endang Windiarti; Walin (Gema Lingkungan Kesehatan, 2026)
Early detection of changes in patients' clinical conditions is very important to prevent critical events. The Early Warning Score (EWS) assessment still relies on conventional tools that require multiple devices and time, which reduces efficiency and accuracy. Objective: To develop and evaluate a portable vital sign measurement tool based on EWS (Vitaltrack EWS) to improve the speed and accuracy of assessments compared to conventional methods. Methods: The study used a Research and Development (R&D) design involving 39 inpatients in the neurology and surgery wards of RSUD Dr. Soedarso Pontianak. Five physiological parameters blood pressure, pulse rate, body temperature, respiratory rate, and oxygen saturation were measured using two methods: conventional tools and Vitaltrack EWS. A t test was used to assess the equivalence or differences in results between the two measurement methods. Results: EWS score p = 0.932, systolic blood pressure p = 0.907, body temperature p = 0.584, heart rate p = 0.487, respiratory rate p = 0.083, oxygen saturation p = 0.487, measurement time p = 0.000. Vitaltrack EWS is assessed to be accurate and efficient in monitoring patients' vital signs, comparable to the standard tools that have been used in hospitals. Conclusion: Vitaltrack EWS is capable of improving the efficiency and accuracy of vital sign measurements and supports the effective implementation of EWS in inpatient settings. Optimization of sensors and applications through further research provides a scientific basis for the feasibility of commercializing the tool.